The Influence Of Customer Relationship Management And Service Quality On Customer Loyalty At JNE Pendowo Branch - Safitri, Nurlita Endah; Masreviastuti, Masreviastuti (SEAN Institute, 2024)
Technological developments have a major influence on people's lives. In its development, shipping companies are also growing rapidly. In the company's marketing strategy, the existence of customer relationship management (CRM) and service quality is an attraction to maintain customer loyalty. The purpose of this study was to examine the influence of customer relationship management variables and service quality on customer loyalty at JNE Pendowo Branch among university students in Malang. The research approach used a quantitative explanatory research approach. Data collection was carried out by distributing questionnaires to 100 respondents who met the research criteria. This research used a purposive sampling technique. The data analysis technique used was descriptive analysis, validity test, reliability test, classic assumption test, and hypothesis testing. The results of this study indicate that customer relationship management and service quality have a positive and significant effect partially or simultaneously on customer loyalty at JNE Pendowo Branch. From this research, it is hoped that JNE Pendowo Branch can maintain and improve customer relationship management and service quality. So, that customers are more loyal to make purchases.